EFFECT OF FINANCIAL PERFORMANCE AND MACROECONOMIC CONDITIONS ON STOCK RETURN LQ45 - Rizky Sukrianingrum, Novita
The LQ45 category is one of the indexes that investors are interested in because it has high liquidity and large market capitalization. In addition to having a high level of liquidity and market capitalization, LQ45 is also safe to transact, because these stocks are generally from large companies with promising fundamentals. However, based on the LQ45 index in the past five years (2013-2017), in 2015 the LQ45 index significantly decreased. It indicates the LQ45 index does not always provide positive returns for the investors. Return on Assets (ROA), Current Ratio (CR), Debt to Assets Ratio (DAR) are measurements of financial performance, and Bank Indonesia Rate (BI Rate), Inflation, Gross Domestic Product Growth (GDP Growth) are measurements of macroeconomic conditions that are factors that affects return stock.